PAR-COM: A new methodology for post-processing association rules - De Carvalho, Veronica Oliveira [UNESP]; Dos Santos, Fabiano Fernandes; Rezende, Solange Oliveira; De Padua, Renan [UNESP] (Springer Nature, 2012)
The post-processing of association rules is a difficult task, since a huge number of rules that are generated are of no interest to the user. To overcome this problem many approaches have been developed, such as objective measures and clustering. However, objective measures don't reduce nor organize the collection of rules, therefore making the understanding of the domain difficult. On the other hand, clustering doesn't reduce the exploration space nor direct the user to find interesting knowledge, therefore making the search for relevant knowledge not so easy. In this context this paper presents the PAR-COM methodology that, by combining clustering and objective measures, reduces the association rule exploration space directing the user to what is potentially interesting. An experimental study demonstrates the potential of PAR-COM to minimize the user's effort during the post-processing process. © 2012 Springer-Verlag.
Keywords: Association rules; Clustering; Objective measures; Post-processing; Experimental studies; Objective measure; Post processing; Information systems